The lying game - Shepard, Sara, 1977- (New York : HarperTeen, 2010)
Seventeen-year-old Emma Paxton steps into the life of her long-lost twin Sutton to solve her murder, while Sutton looks on from her afterlife.
Keywords: Twins -- Fiction; Sisters -- Fiction; Murder -- Fiction; Dead -- Fiction; Impersonation -- Fiction; Mystery and detective stories